Social responses to volcanic eruptions: A review of key concepts. (10th January 2019) - Torrence, Robin
Abstract: A review of key concepts useful for structuring research on social responses to volcanic eruptions among pre-industrial societies is presented as a framework for contextualising research on the Avellino volcanic event. Beginning with vulnerability, the importance for archaeological research of a temporal viewpoint that effectively incorporates studies of resilience, change, and adaptation is appraised. A discussion of the potential effects of volcanic disasters on food procurement is presented to illustrate the value of broadening the scale of research beyond a focus on initial impacts.